Parental socio-economic status, family structure and living environment as predictors of violence against children: empirical evidence from Benin city, Nigeria. (2008)
Violence against children is of concern to the world at large, as a lot of behavioural misnomers have been linked to the experience of children in their growing years. This study adopted a survey research design to investigate how parental socio-economic status, family structure and living environment act as predictors of violence against children; a multistage, random sampling procedure was used to select respondents for the study. Pupils from ten primary schools and six junior secondary schools were selected from Benin City. From each school twenty-five subjects were randomly selected making a total of 400 respondents. The instruments used for data collection were questionnaires tagged "violence against children scale, r=0.80”; "parental socio-economic status scale=0.78"; "family structure scale, r=0.72”; and "living environment scale, r=0.79". Data collected were analyzed using the linear regression procedure and three hypotheses were tested at 0.05 level of significance. The study found that parental socio-economic status, family structure and living environment predicted violence against children. Based on the findings, it was recommended that family support services should be designed to educate parents on how to provide safe and stable family environment for children.